The influence of syringic acid treatment on total dopamine levels of the hippocampus and on cognitive behavioral skills. (2nd September 2022) - Ogut, Eren; Akcay, Guven; Yildirim, Fatos Belgin; Derin, Narin; Aslan, Mutay
Abstract: Background: Natural polyphenols have been investigated and are claimed to be mediators of the relationship between dopamine (DA) and memory. Therefore, we aimed to measure and evaluate the effect of syringic acid (SA) on DA expression by behavioral tests related to short-term and recognition memory in Wistar rats. Methods: Rats were randomly assigned to control (0.5 cc corn oil, n = 10), SA (25 mg/kg/day, o.g, n = 10), Deltamethrin (DTM) (1.28 mg/kg/day o.g, n = 10) and DTM (1.28 mg/kg/day o.g, n = 10) + SA (25 mg/kg/day) groups. The Y-maze and Novel Object Recognition (NOR) tests were performed to assess cognitive and behavioral functions in the rats. Dopamine levels in the hippocampus were measured by mass spectrometry. Results: Syringic acid significantly increased DA (5.45 ± 1.06 ng/ml, p = 0.0026, p < 0.05) compared with the other groups. SA increased the percent alternation (34.85 ± 0.72%, p < 0.05), time spent in the novel arm (2.88 ± 0.18 min, p < 0.05), and frequency of novel arm entries (44.91 ± 2.28%, p < 0.05), of the rats after the Y-maze test. The SA elevated the discrimination index (70.42 ± 3.59%, p < 0.001), and exploration time (30.44 ± 1.8 sec, p < 0.05) in the NOR test, and increased the short term and recognition memory in behavioral tests. Conclusion: Our findings support the hypothesis that SA-induced DA levels of the hippocampus may facilitate recognition and short-term memory in Wistar rats through the activation of dopaminergic receptors or pathways during the learning process, and that this can be seen in the cognitive behavior of SA-treated rats.